The Effect of Motivation, Tax System Complexity, and Financial Conditions on Taxpayer Compliance - Firna Muflihani; Bambang Subroto; Mohamad Khoiru Rusydi (Journal of Economics, Business, and Accountancy Ventura, 2021)
This study was conducted to determine the factors that influence the behavior of taxpayer compliance through tax planning, both internal and external factors. This study used analytical method of SEM (Structural Equation Modeling) with sample consisting of 346 corporate taxpayers and tax professionals in Samarinda City as the unit of analysis. Data were collected by distributing questionnaires either directly or via Google form. The results of this study prove that internal factors have a negative effect on obedient behavior directly and have a positive effect on tax-payer compliance through tax planning. This study also proves that external factors have a positive effect on tax-payer compliance both directly and through tax planning. Therefore, it can be concluded that the motivation for tax compliance is mediated perfectly by tax planning. Meanwhile, the complexity of the taxation system and the financial condition of taxpayer compliance is partially mediated by tax planning. The results of this study imply the importance of tax planning in increasing tax payments.